Dust-producing weather patterns of the North American Great Plains - S. Evans (Atmospheric Chemistry and Physics)
The North American Great Plains is a semi-arid and windy environment prone to dust events that produce a variety of hazards to public health, transportation, and land degradation. Dust has substantial spatial variability across the plains, and the weather responsible for that dust is understudied in most of the plains, especially the northern and eastern plains. Here we identify specific weather patterns associated with dust occurrence across the plains. We make use of an atmospheric classification that defines 21 weather patterns for the Great Plains that includes various stages of warm and cold frontal passages, northerlies, anticyclones, and summertime patterns not associated with mid-latitude cyclones. We use the time series of weather pattern to composite satellite and station daily dust observations from 2012–2021. We calculate average dust occurrence for each weather pattern, calculate the contribution of each pattern to local dust loads, and identify the specific weather patterns most important to each location and subregion. We find no single weather pattern is responsible for dust occurrence in the plains but that different patterns are responsible for dust in different subregions of the Great Plains. Passing cold fronts are most responsible for dust events in West Texas and New Mexico, southerlies are responsible for those in the northeastern plains of Iowa and the Dakotas, and summer weather patterns produce the majority of dust in the High Plains from Colorado to Canada. Identifying the dust-producing weather patterns of particular subregions is a valuable step toward understanding dust variability and improving dust predictions, both present and future.